VD_FINDINFO Jug / 2012 / 11 vom 21. September 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, PENSION D'ASSISTANCE | 217 al. 1 CP, 32 CP, 34 CP, 44 CP, 47 CP, 428 al. 1 CPP (CH), 433 al. 2 CPP (CH)